TRANSFORMATION OF ISLAMIC RELIGIOUS EDUCATION IN THE DIGITAL ERA: CHALLENGES AND OPPORTUNITIES - Ridlo, Muhammad 'Ainur; Gunawan, Zaini; Lawal, Uthman Shehu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Study This aims to analyse the transformation of Islamic religious education at Namira Middle School, Probolinggo, through a contextual approach to integrating technology and applying hybrid learning models. This study aims to explore digital technology's impact on Islamic religious learning and identify school challenges and opportunities. The research method used is qualitative descriptive with approach studies case, which involves interviews, observations, and documentation as technique data collection. Research results show that integration technology in Islamic religious learning through a contextual approach impacts the improved involvement of students. Technology is used to make it easier to access material and convey material more enjoyably and interactively, such as through learning videos and online modules. In addition, the hybrid learning model combines face-to-face and online learning to allow students to access the material anywhere and anytime while still guarding interaction straight to the point: To understand Islamic religious values. However, the main challenge faced is the gap in access to technology among students, who need to overcome it so that technology can be accessed evenly. Thus, implementing the second approach succeeds in being more holistic and applicable, improving the understanding of Islamic teachings and supporting character development. Research This recommends the development of more carry-on from the second approach to optimise Islamic religious education in the digital era.